Phenomenon of Graphic Substitution in Internet Discourse (Proceedings of Southern Federal University. Philology, 2019)
Elena A. Kalinovskaya, Anna S. Kobysheva (Stavropol, Russian Federation)The article is devoted to the study of graphic substitutes in the language of Internet communication. The authors identified and described the main ways of graphical transformation of language phenomena at the level of supragraphics, syngraphics and changing the letter composition of a word. The following means of graphic substitution in virtual discourse are distinguished: font variation, punctuation marks, alphabetic and «nonletter» symbols.Key words: graphical substitution, graphic substitute, virtual communication, Internet communication.DOI 10.23683/1995-0640-2019-1-91-98